Three Purāṇic Statements on the Shape of the Earth - Knudsen, Toke Lindegaard (History of Science in South Asia, 2021)
The article analyses an argument given in Jñānarāja's Siddhāntasundara (ca. 1500) on the shape of the earth according to the Purāṇas. The argument involves the use of the word gola, 'ball, globe,' in the Purāṇas, a Purāṇic statement about the mountain Meru being north of everywhere, and a Purāṇic comparison of the earth to a mirror. The article concludes that Jñānarāja breaks with the Purāṇas as well as the traditional commentaries on these texts, and further suggests that we might have to rethink the dictionary definition of gola.